Совершенствование нормативной базы по долгосрочной эксплуатации и управлению старением энергоблоков АЭС - Костенко, С.П. (Ядерна та радіаційна безпека, 2015)
Представлена схема совершенствования нормативной базы по долгосрочной эксплуатации и управлению старением энергоблоков АЭС с учетом рекомендаций МАГАТЭ и мировой практики, а также опыта, накопленного при обосновании долгосрочной эксплуатации энергоблоков №№ 1 и 2 Ровенской АЭС и № 1 Южно-Украинской АЭС. Показана связь нормативных и технических документов при выполнении работ по долгосрочной эксплуатации и управлению старением энергоблоков АЭС. Наведено схему вдосконалювання нормативної бази з довгострокової експлуатації та управління старінням енергоблоків АЕС з урахуванням рекомендацій МАГАТЕ і світової практики, а також досвіду, придбаного у процесі обґрунтування довгострокової експлуатації енергоблоків №№ 1 та 2 Рівненської АЕС і № 1 Южно-Української АЕС. Показано зв’язок нормативних і технічних документів при виконанні робіт з довгострокової експлуатації та управління старінням енергоблоків АЕС. The regulatory framework for long-term operation and ageing management of NPP units in Ukraine was reviewed and deficiencies were identified. The procedure for improving regulatory framework for long-term operation and ageing management is presented. It takes into consideration IAEA recommendations and international practices, as well as experience obtained in long-term operation efforts for Rivne NPP-1, 2 and South Ukraine NPP-1. The paper demonstrates interrelations between standards and technical documents on long-term operation and ageing management. The information is presented regarding the current state of regulatory and legal documentation development and industry-specific standards on long-term operation and ageing management of NPP units in Ukraine.